Path Analysis: Application of Health Belief Model on the Determinants of Clean and Healthy Behavior among Elderly with Hypertension - Septian Najib Imtichan; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Promotion and Behavior, 2019)
Background: Lifestyle or behavioral factors critically determine high blood pressure in individuals. Elderly with hypertension in Indonesia aged 55-64 years by 45.9%, 65-74 years by 57.6%, and > 75 years by  63.8%. This study aimed to examine factors affecting healthy behavior in elderly with hypertension using the health belief model.Subjects and Method: This was a cross-sectional study conducted in Ngawi, East Java, from June to July 2019. A sample of 200 elderly was selected by multistage random sampling. The dependent variable was clean and healthy behavior. The independent variables were perceived susceptibility, perceived severity, perceived benefit, cues to action, self-efficacy, knowledge, attitude, and access to health service. The data were collected by questionnaire and analyzed by path analysis.Results: Clean and healthy behavior was positively and directly affected by self-efficacy (b= 1.51; 95% CI= 0.29 to 2.74; p= 0.015), attitude (b= 2.37; 95% CI = 1.17 to 3.56; p<0.001) , cues for action (b = 2.48; 95% CI= 1.11 to 3.86; p <0.001), perceived susceptibility (b= 2.07; 95% CI= 0.89 to 3.26; p= 0.001), perceived severity (b= 1.76; 95% CI= 0.54 to 2.99; p= 0.005), perceived benefit (b= 1.47; 95% CI= 0.36 to 2.57; p = 0.009), and access to health services (b= 2.26; 95% CI= 1.00 to 3.53; p<0.001). Clean and healthy behavior was indirectly affected by knowledge.Conclusion: The clean and healthy lifestyle behavior of the elderly is directly affected by the perceived vulnerability, perceived severity, perceived benefits, cues to act, self-efficacy, attitudes, and access to health services. Clean and healthy behavior is affected by knowledge.Keywords: clean and healthy behavior, elderly, health belief model, path analysisCorrespondence:Septian Najib Imtichan. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 54176, Central Java. Email: septianimtichan@gmail.com.Mobile: +6285229799672Journal of Health Promotion and Behavior (2019), 4(2): 110-120https://doi.org/10.26911/thejhpb.2019.04.02.03